Major abdominal surgery in a patient with a metallic heart valve—balancing risks of thromboembolic events and perioperative bleeding - Parizh, David; Kumar, Sampath; Meytes, Vadim (Digestive Medicine Research, 2018)
Surgical patients with mechanical valves are challenging, as their need for anticoagulation to reduce thromboembolic events is weighed against the risk for postoperative hemorrhage. Timing and bridging method for anticoagulation presents a great challenge for the surgeon. There is no protocol and consensus to our knowledge of managing acute major abdominal surgery in patients with metallic valves. We share our experience and review the current literature on this topic.